na dziś daje naj hshs​



Na Dziś Daje Naj Hshs class=

Odpowiedź :

Odpowiedź:

Zestaw I

n² - 3n(n + 2) = n² - 3n² - 6n = -2n² - 6n

-5n(-2n + 3) - 3n(4n - 3) = 10n² - 15n - 12n² + 9n = -2n² - 6n

-4n(n - 2m + 3) - 2n(-n + 3m - 5) - 2n(m + 2) = -4n² + 8mn - 12n + 2n² - 6mn + 10n - 2mn - 4n = -2n² - 6n

Zestaw II

x² + 4x(3y - x) + 6y(y - 2x) = x² + 12xy - 4x² + 6y² - 12xy = -3x² + 6y²

2x(y - 1,5x) - 3y(-2y + [tex]\frac{2}{3}[/tex]x) = 2xy - 3x² + 6y² - 2xy = -3x² + 6y²

-x(3y² - 4[tex]\frac{1}{2}[/tex]x) + (5x²-3y²) * (-1,5) - 3y(-xy - [tex]\frac{1}{2}[/tex]y) = -3xy² + 4,5x² - 7,5x² + 4,5y² + 3xy² + 1,5y² = -3x² + 6y²

Zestaw 3

-3a² + 2a(a - 4) = -3a² + 2a² - 8a = -a² - 8a

a(3 - a) - 2,75(4a - 3) - 8[tex]\frac{1}{4}[/tex] = 3a - a² - 11a + 8,25 - 8,25 = -a² - 8a

(3a² - 4ab) * (-5) - 4b(2a - ab) - 2a(4 - 7a + 6b + 2b²) = -15a² + 20ab - 8ab + 4ab² - 8a + 14a² - 12ab - 4ab² = -a² - 8a

Zestaw 4

p(4p - 5s) - s(-5p + 2s) = 4p² - 5ps + 5ps - 2s² = 4p² - 2s²

2p(2p - s) - s(p - s) * (-2) = 4p² - 2ps -(ps - s²) * (-2) = 4p² - 2ps + 2ps - 2s² = 4p² - 2s²

[tex]\frac{2}{3}[/tex]p(6p - 2s + 4) - [tex]\frac{1}{6}[/tex]s(1 + 12s - 8p) - [tex]\frac{1}{3}[/tex](8p - [tex]\frac{1}{2}[/tex]s) = 4p² - [tex]\frac{4}{3}[/tex]ps + [tex]\frac{8}{3}[/tex]p - [tex]\frac{1}{6}[/tex]s - 2s² + [tex]\frac{8}{6}[/tex]ps - [tex]\frac{8}{3}[/tex]p  + [tex]\frac{1}{6}[/tex]s = 4p² - 2s²

Inne Pytanie